1990
DOI: 10.1159/000200376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Massive Small Bowel Resection on Components of the Peptidergic Innervation of the Rat Small Intestine

Abstract: The effect of massive small bowel resection on the immunostaining of neuropeptides in the submucous plexus of the retained small intestine was examined. The neuropeptides chosen were somatostatin and vasoactive intestinal polypeptide because these are markers for two of the major populations of neurons in the plexus. Three different methods were used to assess the effect of resection on the enteric nervous system. Firstly immunocytochemical staining of neuropeptide containing neurons and nerve fibers was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…This supports previous findings that luminal nutrients are a major stimulus for mucosal cell proliferation and intestinal adaptation (10,32). Luminal nutrients increase pancreaticobiliary secretions, gut neuronal/vagal activity, splanchnic blood flow, and secretion of hormones that may stimulate gut growth directly or indirectly (6,14,21).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This supports previous findings that luminal nutrients are a major stimulus for mucosal cell proliferation and intestinal adaptation (10,32). Luminal nutrients increase pancreaticobiliary secretions, gut neuronal/vagal activity, splanchnic blood flow, and secretion of hormones that may stimulate gut growth directly or indirectly (6,14,21).…”
Section: Discussionsupporting
confidence: 89%
“…The interactions between luminal nutrients and neuroendocrine signals in the stimulation of intestinal adaptive growth are poorly understood; however, GLP-2 is thought to be a key hormonal mediator (6,10,13,21,36,42). We have investigated how partial functional ablation of vagal afferent input Values are means Ϯ SE; n ϭ 9 -13 rats group.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the correlation of nNOS with crypt cell kinetics and muscle thickness was consistent with other reports demonstrating a regulatory role for nitric oxide and the myenteric plexus in jejunal crypt cell proliferation [41, 42]. Although we did not detect any changes in the ratio of VIP staining neurons, previous studies have described inhibitory and stimulatory effects of proximal and mid bowel resection on VIP abundance in the ENS [43, 44]. Inconsistencies in results could be due to the absence of transected bowel controls, or the effect of location and extent of resection on specific neuroeffectors [4346].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the previous studies reported more than once that strong pathological stimuli, which are known to influence the neurochemical characterization of the enteric neurons, have no effect on the number of SOM-immunoreactive nervous structures in the GI tract. Such a situation has been noted, among others, in the human colon during Hirschsprung disease [54], within the human pylorus during hypertrophic pyloric stenosis [21], and after massive bowel resection in the rat small intestine, although in the latter case a clear increase in the size of SOM-positive enteric neurons was reported [95]. A summary of the existing observations concerning the changes in the number of SOM-positive nervous structures in the wall of the GI tract under various stimuli is presented in Table 2.…”
Section: The Plasticity Of the Enteric Nervous Structures Containimentioning
confidence: 83%